Asuhan Keperawatan Jiwa Pada Ny. N Dengan Masalah Utama Risiko Perilaku Kekerasan Akibat Skizofrenia Tak Terinci Di Ruang Citroanggodo RSJD dr. Amino Gondohutomo Provinsi Jawa Tengah - Hishni Munaza; Titi Sri Suyanti (STIKES Columbia Asia Medan, 2026)
Background: Schizophrenia is a serious mental disorder characterized by disturbances in thought processes, emotions, and behavior. One of the positive symptoms that can occur in schizophrenic clients is the risk of violent behavior. Risk of violent behavior is one of the nursing diagnoses frequently found in the Citroanggodo Ward of RSJD dr. Amino Gondohutomo, Central Java Province. Therefore, the author conducted psychiatric nursing care for Mrs. N with the main problem of risk of violent behavior due to undifferentiated schizophrenia. Methods: The writing method used is descriptive with a case study approach. Data collection was carried out through interviews, observation, documentation studies, and literature studies. The general objective of this Scientific Paper is to provide nursing care to patients with Risk of Violent Behavior due to Undifferentiated Schizophrenia. Results: The nursing diagnoses that emerged in the patient with Risk of Violent Behavior due to Undifferentiated Schizophrenia were: Risk of Violent Behavior, Self-Concept Disorder: Low Self-Esteem, and Self-Care Deficit. Nursing interventions carried out included SP 1 through SP 4 for Risk of Violent Behavior and SP 2 for Self-Care Deficit. Conclusion: After 8 days of nursing implementation, of the 3 diagnoses raised, 1 diagnosis was partially resolved (risk of violent behavior), 1 diagnosis was resolved (self-care deficit), and 1 diagnosis was not implemented (self-concept disorder: low self-esteem).